Pet-health as a tool for identifying stress levels in primary healthcare professionals - Dalagnol A.M.K. (2023)
© 2023 Faculdade de Medicina de Ribeirao Preto - U.S.P.. All rights reserved.Evidenced today that working conditions can contribute to changes in the physical and mental health of individuals, studies point to the relationship of these disorders with dissatisfaction, lack of professional recognition, exhaustion caused by direct contact with the patient, insufficient rewards, lack of autonomy, dysfunctional interpersonal relationships, conflict of values, lack of human and material resources, long working hours, low pay, narrowing of the labor market, high exposure to occupational risks and the lack of definition of the professional role. The research emerged from the initial experiences of the PET-Saúde Interprofissionalidade project. Objective: Analyze stress levels among professionals at a Family Health Center (FHC), through the application of the Lipp test - Lipp Stress Symptoms Inventory (ISSL). Methodology: A quantitative, descriptive, transversal research was carried out. Thirty professionals who worked in the service participated in the research. Results: Of the professionals evaluated, 6.7% were in the alert phase, 56.6% in the resistance phase and 16.7% in the exhaustion phase. The most identified symptoms were physical, since the psychological symptoms found are intrinsic and identified through information given by professionals. Conclusion: In this way, it is necessary to carry out strategies for the prevention and control of disorders that affect and/or tend to affect these professionals, thus improving their quality of life, as well as assistance to users.